Case report: Autoimmune encephalitis with multiple auto-antibodies with reversible splenial lesion syndrome and bilateral ovarian teratoma - Li, Yaqiang; Zhang, Mei; Liu, Deshun; Wei, Ming; Sheng, Jun; Wang, Zhixin; Xue, Song; Yu, Tingting; Xue, Weimin; Zhu, Beibei; He, Jiale (Frontiers in Immunology, 2023)
Background: Reversible splenial lesion syndrome (RESLES) is a spectrum of disease radiologically characterized by reversible lesions due to multiple causes, mainly involving the the splenium of the corpus callosum (SCC). The most common causes of RESLES are infection, antiepileptic drugs use, antiepileptic drugs withdrawal, and severe metabolic disorders. It is rare, nevertheless, to mention cases of autoimmune encephalitis (AE). Case Presentation: A 26-year-old female computer programming engineer with no past medical or psychiatric history presented to the psychiatric hospital due to a 3-day episode characterized by irritability, babbling, stiffness of the limbs, sleepwalking, hallucinations and paroxysmal mania. Her brain MRI revealed abnormal signals of the SCC. An antibody testing of CSF using a cell-based assay in combination with a tissue-based assay was applied. The anti-NMDAR (titer of 1:3.2) antibody was detected as positive. Serum studies were also performed, demonstrating positive anti-NMDAR (titer of 1:32), anti-mGluR5 (titer of 1:10). Her conditions considerably improved after intravenous steroids and immunoglobulin. Ovarian teratoma was considered after pelvic CT. A follow-up MRI scan indicated the lesion in the SCC had completely resolved 2 weeks after discharge. Enhanced CT of the pelvis showed an enlarged pelvic mass, and bilateral ovarian teratomas (mature teratoma and immature teratoma ) were considered, which were then pathologically confirmed after transabdominal left adnexal resection, right ovarian biopsy, and ovarian cystectomy. Afterward, she received standard 3 cycles of bleomycin, etoposide, and cisplatin (BEP). She experienced complete resolution of symptoms without any sign of recurrence and tumors during a 1-month follow-up. The anti-mGluR5 antibody in the serum and the anti-NMDAR antibody in the CSF turned negative, respectively, yet the titer of the anti-NMDAR antibody in the serum remained 1:32. Conclusion: Our findings suggested that clinicians should be aware that focal reversible lesions in the SCC may be seen in patients with multiple co-existing antibody-positive AE. The anti-NMDAR and anti-mGluR5 antibodies could be mechanistically linked to the RESLES. Anti-NMDAR and anti-mGluR5 antibodies should be added the potential list of causes of RESLES, and similarly, RESLES may be added to the many potential clinical and radiographic presentations of multiple co-existing antibodies.